2018
DOI: 10.1007/s10286-018-0572-5
|View full text |Cite
|
Sign up to set email alerts
|

The renin–angiotensin system in cardiovascular autonomic control: recent developments and clinical implications

Abstract: Complex and bidirectional interactions between the renin-angiotensin system (RAS) and autonomic nervous system have been well established for cardiovascular regulation under both physiological and pathophysiological conditions. Most research to date has focused on deleterious effects of components of the vasoconstrictor arm of the RAS on cardiovascular autonomic control such as renin, angiotensin II, and aldosterone. The recent discovery of prorenin and the prorenin receptor have further increased our understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
149
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(156 citation statements)
references
References 107 publications
(156 reference statements)
1
149
0
6
Order By: Relevance
“…This result suggested that other systems might be compensating for the low levels of ANP in Pam Myh6-cKO/cKO mice. The renin-angiotensin system increases blood pressure by stimulating the conversion of angiotensinogen to angiotensin I; renin secretion is stimulated by low blood sodium and sympathetic input and suppressed by ANP (56). However, assays for serum renin levels in WT and Pam Myh6-cKO/cKO mice on a normal salt diet revealed no difference (Fig.…”
Section: Anxiety-like Behavior and Thermoregulation Are Altered Inmentioning
confidence: 96%
“…This result suggested that other systems might be compensating for the low levels of ANP in Pam Myh6-cKO/cKO mice. The renin-angiotensin system increases blood pressure by stimulating the conversion of angiotensinogen to angiotensin I; renin secretion is stimulated by low blood sodium and sympathetic input and suppressed by ANP (56). However, assays for serum renin levels in WT and Pam Myh6-cKO/cKO mice on a normal salt diet revealed no difference (Fig.…”
Section: Anxiety-like Behavior and Thermoregulation Are Altered Inmentioning
confidence: 96%
“…Angiotensin-converting enzyme 2 (ACE2) is a cardio-cerebral vascular protection factor existing in a variety of organs, including the nervous system and skeletal muscles, playing a major role in regulating blood pressure and anti-atherosclerosis mechanisms (Miller and Arnold, 2019). Meanwhile, ACE2 is also an important target for various CoV and influenza viruses (Turner et al, 2004;Wrapp et al, 2020;Yang et al, 2014).…”
Section: Angiotensin-converting Enzymementioning
confidence: 99%
“…Angiotensin-converting enzyme 2 can catalyse the conversion of angiotensin (Ang) II into Ang-(1-7), and the latter can act on the Mas receptor, then play a crucial role in cardiovascular protection, such as regulating blood pressure, anti-atherosclerosis, inhibiting fibrosis, and improving heart function. 56,57 Unexpectedly, ACE2 is also a vital target for a variety of coronaviruses and influenza viruses. 58,59 Liu et al 60 reported that the influenza neuraminidase of H1N1 viruses could directly cleave the ACE2 protein and then degrade it via proteasome pathway, so ACE2 protein levels were significantly down-regulated after being infected with H1N1 viruses.…”
Section: Angiotensin-converting Enzymementioning
confidence: 99%